GamaBox-One: A Proposed Architecture for Cloud-based Big Data Management Platform for Multipurpose Computation using Hybrid Architecture - Riasetiawan, Mardhani; Ashari, Ahmad; Priyambodo, Tri Kuntoro; Suyanto, Yohannes; Prastowo, Bambang Nurcahyo; Rouf, Abdul; Timur, Idham Ananta; Widodo, Triyogatama Wahyu; Mujiyatna, I Gede; Saputro, Bagaskoro (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The architecture of the data center is the main key for producing a highly functional demand big data management platform for multipurpose uses. Nowadays various technologies have come to provide construction of that purpose, providing several use cases for big data analytics and processing. In this paper, we want to explore possibilities of architecture that had to be built in answer to the multipurpose data center, such as analytical research, scientific simulation, machine learning, deep data learning, and data orchestration. We discover how Hadoop and its element supporter can be used alongside cloud orchestrators such as Terraform or Occopus and container orchestrators such as Kubernetes or Docker Swarm. We also provide possible supporting components that can handle the different jobs in High-Performance Computing and how the system can be secured. Our proposed approach in this research has developed the architecture for cloud-based big data management for multipurpose computation.